2016
DOI: 10.1080/15402002.2016.1188393
|View full text |Cite
|
Sign up to set email alerts
|

Do People With Chronic Pain Judge Their Sleep Differently? A Qualitative Study

Abstract: 39People with chronic pain often report sleep of "poor quality".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…The development of hybrid treatments for chronic pain and insomnia is only in its infancy, but it is certainly a movement gaining momentum at a time when the term 'secondary insomnia' is being phased out (94) and epidemiological evidence is accumulating to show that sleep is a risk factor and a potential cause of a range of physical and mental illnesses, directly and indirectly increasing the risk of mortality (95). The momentum is also bolstered by demands from the pain patients themselves, explicitly stating the negative impact on pain management when they are not sleeping well (96,97) and indicating that their wish to receive more support and help in obtaining better sleep (9,98,99).…”
Section: Recent Development In Pain and Insomnia As An Examplementioning
confidence: 99%
“…The development of hybrid treatments for chronic pain and insomnia is only in its infancy, but it is certainly a movement gaining momentum at a time when the term 'secondary insomnia' is being phased out (94) and epidemiological evidence is accumulating to show that sleep is a risk factor and a potential cause of a range of physical and mental illnesses, directly and indirectly increasing the risk of mortality (95). The momentum is also bolstered by demands from the pain patients themselves, explicitly stating the negative impact on pain management when they are not sleeping well (96,97) and indicating that their wish to receive more support and help in obtaining better sleep (9,98,99).…”
Section: Recent Development In Pain and Insomnia As An Examplementioning
confidence: 99%
“…Sleep and mood are therefore central components both in expression of illness, and as part of the multimodality treatment of chronic pain patients. There is emerging evidence that chronic pain patients with comorbid sleep problems are aware of the bidirectional relationship between the constructs (Tang et al, 2009; Ramlee et al, 2016). Hence, there is great potential in assessing and utilizing attributions to aid accurate understanding and treatment of chronic pain and its comorbid conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 18 , 21 , 26 , 27 , 36–38 The selection of parameters was also informed by themes that emerged from a recent qualitative study conducted by our group, in which we explored the criteria people use to judge their sleep quality. 28 In this study, we found that people by and large rely on their (1) memories of nighttime sleep disruptions, (2) feelings on waking and cognitive functioning during the day, (3) ability to engage in daytime physical and social activity, and (4) changes in physical symptoms as key criteria for evaluating their sleep quality. Accordingly, the chosen parameters were not restricted to the sleep period, but included factors that spanned from the day before the sleep period to the day after.…”
Section: Methodsmentioning
confidence: 82%
“…For example, in our research with people with chronic pain and comorbid insomnia, we found that patients considered pain and discomfort in the morning and how much they can physically do during the day as the most important indicators of sleep quality of the night before. 28 …”
Section: Introductionmentioning
confidence: 99%